PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN INDOMIE GORENG MELALUI BRAND IMAGE SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA MAHASISWA S1 FISIP UNDIP SEMARANG) - Dinda Annisa Parasayu; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2016)
Instant noodles is a product that is preferred by consumers in the world because of practicality. It is therefore necessary for the company to analyze consumer behavior to determine the product purchase patterns. This research aims to determine whether the model of this research is acceptable or not. The model of this research is testing the influence of product quality and promotion to purchasing decisions on brand image as an intervening variable. Instant noodle is very popular among the college students, especially who lived inboarding houses. For them, the instant noodles is the right choice for consumptionas it is very easy to process and practical. For that researchers will conduct a survey on S-1 Degree of FISIP Undip in particular. Total sample of 100 respondent by using accidental and purposive sampling. The measurement scale using Likert. The data analysis using measurement outer model, inner model, direct effect, indirect effect, Variance Accounted For (VAF) methods, and model of indices.The direct effect and indirect effect in this research are prove to give an significant effect. According to VAF method shows that the brand image is included in partial mediation. The output model of indices shows that the model already fulfill the goodness of fit. Based on this research, is suggested that company PT Indofood Sukses Makmur, Tbk did repair and improvement on the quality of good quality flavors, packaging, nutrient content in the product, as well as making corporate social activity or event in order to form a positive image of the company and products so the brand image on fried indomie remain good in the minds of consumers and engender the trust and love of the brand so that later the purchase decisions of fried indomie high and can create advantages for the companies that produce it.